Pyogenic granuloma of the larynx. Issue 7 (4th July 2022) - Hijazi, Leen Omar; Asiri, Mohammed; Al Mahdi, Mohammed Jihad; Pharaon, Majed
Abstract: Pyogenic granulomas are benign, typically painless, vascular tumors of the skin and mucosal surface. Recently the term 'lobular capillary hemangioma' has been introduced to describe the histological appearance more accurately. Major locations for pyogenic granuloma are in the head and neck region, but larynx localization is rare. In this case report, we present a case of a 36-year-old male with lobular capillary hemangioma of the larynx and discuss the related literature.